MAWLID CELEBRATION IN ACEH: Culture, Religious Expression, and Political Medium - Shadiqin, Sehat Ihsan; Ikramatoun, Siti (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2022)
Abstract: This study is an ethnographic note about the Mawlid celebrations in Aceh. In contrast to most studies by previous scholars who saw Mawlid as a medium for normative theological discourse, this article aims to narrate the Mawlid phenomenon by focusing on how the Acehnese celebrated Mawlid, how the religious expression was, and how Mawlid became a political medium. This study showed that the Mawlid celebration in Aceh is not just a tradition or an expression of love for the Prophet but a cultural construction inherent to the Acehnese society, religious expression, and political media. Mawlid as a cultural construction is manifested in various forms of unique food dishes, as a religious expression manifested in typical Dhikr and Lectures Mawlid, and as a political medium seen from the invitations of Mawlid, Mawlid Pemda, and Mawlid at home.Keywords: Acehnese; Mawlid Celebration; Culture; Social Identity; Religious Expression; Political Medium.